2008
DOI: 10.1097/sap.0b013e318166d351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight Loss Surgery and Body Mass Index on Wound Complications After Abdominal Contouring Operations

Abstract: Abdominal contouring operations are in high demand after massive weight loss. Anecdotally, wound problems seemed to occur frequently in this patient population. Our study was designed to delineate risk factors for wound complications after body contouring. Our retrospective institutional analysis was assembled from 222 patients between 2001 and 2006 who underwent either abdominoplasty (N = 89) or panniculectomy (N = 133). Weight loss surgery (WLS) before body contouring occurred in 63% of our patients. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 25 publications
8
68
0
5
Order By: Relevance
“…Consequently, the pathogenic bacteria which thrive in the moist environment of skin folds have an ideal environment for invasion and tissue breakdown. Lastly, skin-on-skin contact causes friction that can lead to ulceration that are particularly frequent in obese individuals [76,86,87].…”
Section: Imbalanced Diet Is Critical For the Physiologic Wound Healingmentioning
confidence: 99%
“…Consequently, the pathogenic bacteria which thrive in the moist environment of skin folds have an ideal environment for invasion and tissue breakdown. Lastly, skin-on-skin contact causes friction that can lead to ulceration that are particularly frequent in obese individuals [76,86,87].…”
Section: Imbalanced Diet Is Critical For the Physiologic Wound Healingmentioning
confidence: 99%
“…Pre-body contouring BMI [2-4, 6, 7], percentage excessive weight loss [5], smoking [8][9][10], diabetes mellitus and/or hypertension [8], nutritional deficiency [11] ASA classification [5], total amount of removed tissue [4,7], intra-operation time, multiple procedures, maximum BMI and change in BMI from maximum to current BMI [12] are mentioned variable as risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…There are data indicating that the complication rates are higher in post bariatric patients compared to patients who have lost weight following dieting, despite similar preoperative BMI in both groups (55). It has been suggested that malnutrition in post bariatric patients may be a possible explanation of these findings (54). The risk of complications also tends to be higher with combined procedures compared to …”
Section: Complications Of Body Contouring Surgerymentioning
confidence: 72%
“…The corresponding data for patients who have not undergone bariatric surgery tends to be lower (22-29%) (54,55). There are data indicating that the complication rates are higher in post bariatric patients compared to patients who have lost weight following dieting, despite similar preoperative BMI in both groups (55).…”
Section: Complications Of Body Contouring Surgerymentioning
confidence: 88%